Construction and demolition waste management - Jasek, Wiktoria; Szafraniak, Dominik; Głowacka, Anna; Zemski, Łukasz; Bednarek, Roman (Instal, 2025)
saves money and reduces environmental destruction. The article discusses how much construction waste is generated in Poland compared to other countries associated in the European Union. The waste hierarchy is indicated and the proportions of materials obtained from demolition are given. In the article, an analysis was conducted on the waste generated from the demolition of a sports facility, determining the types of materials and their proportions based on the data contained in the Waste Transfer Notes provided by the demolition company. The collected information enabled the identification of predominant types of waste expected from the demolition of structures with similar construction technologies and intended purposes. The findings indicated that the largest volume of waste removed in this instance comprised soil and earth, followed by concrete rubble, brick debris, and mixed materials, the proportions of which may vary significantly depending on the type of structure being demolished. The expected weight of waste was determined, broken down into individual waste fractions for facilities with identical construction technology.